2007
DOI: 10.3176/oil.2007.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Oil Shale Ash as a Constituent of Cement

Abstract: Physical and chemical characteristics of ashes formed at burning oil shale at temperatures 500, 600, 700, 800, 900 and 1030 °C were studied. Standard procedures were used to determine both pozzolanic activity and binding parameters. The most suitable characteristics were provided with oil shale ash formed at 700 °C. Ashes (15 and 30%) were added to ordinary Portland cement. The optimum pozzolanic characteristics and performances were provided by the mixture containing 15% ashes. The mixes meet the correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…It was found that the values of compressive strength of specimens show a dramatic increase at 28 days than those at 7 days of hardening in terms of the effect of adding OSA contents. The mechanical characteristics of ashes obtained from oil shale of the El-Lujjun deposit are in agreement with the results obtained in previous studies [14][15][16].…”
Section: Effect Of Oil Shale Ash Contentsupporting
confidence: 91%
“…It was found that the values of compressive strength of specimens show a dramatic increase at 28 days than those at 7 days of hardening in terms of the effect of adding OSA contents. The mechanical characteristics of ashes obtained from oil shale of the El-Lujjun deposit are in agreement with the results obtained in previous studies [14][15][16].…”
Section: Effect Of Oil Shale Ash Contentsupporting
confidence: 91%
“…Furthermore, OSA as a cement substitute in pastes and mortars has been limited to 20%-all grades are in % by weight of cement from now on [36,37,44,46]. Other studies, on the other hand, have used OSA as an addition in pastes and concretes, varying its concentration between 15%wc and 30%wc [34,40,42]. In this context, it was shown that increasing the ash content reduced the concrete's compressive strength [39,41,42].…”
Section: Osa Contentmentioning
confidence: 99%
“…The OS burning temperature is critical for obtaining an OSA with a uniform composition because shale from different regions has different geological characteristics, i.e., equal burning temperature ranges can produce ashes with different chemical compositions [40]. Even so, OS combustion represents an opportunity to standardize the physical and chemical characteristics of the OSA.…”
Section: Os Burning Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Since it can cause environmental pollution, attempts were made to benefit from such material, especially in construction industries and chemical industries. Previous experimental results indicated that oil-shale ash formed at temperatures ranging from 600 to 800 °C has a cementing strength. Its replacement of cement, sand, or both within cement mortar or concrete specimens by about 10 wt % would yield the optimum compressive strength for cement mortar or concrete, and its replacement of cement by up to 30 wt % would not reduce the compressive strength significantly .…”
Section: Introductionmentioning
confidence: 99%